Motivations for Corporate Social Action - Buehler, Vernon M.; Shetty, Y. K. (Academy of Management Journal, 1974)
The article looks at a study exploring the motivations that large corporations cited for their socially responsible actions in urban, consumer and environmental affairs. The study asked for firms to compare the importance of specific motivations when making decisions regarding the three given categories of social involvement. Forestalling violence and generating profit were the most important motivators cited. Legal compliance and the creation of a positive corporate image were reported as being less important.